Q. 6 A4.4( 10 Votes )

# Show that

Solving L.H.S. first,

(3x + 7)2 – 84x

We know that

(a+ b)2 = a2 + b2 + 2a×b

(3x + 7)2 – 84x = ((3x)2 + (7)2 + 2×3x×7) – 84x

(3x + 7)2 – 84x = 9x2 + 49 + 42x – 84x

(3x + 7)2 – 84x = 9x2 + 49 – 42x

(3x + 7)2 – 84x = ((3x)2 + (7)2 – 2×3x×7)

Using (a– b)2 = a2 + b2 – 2a×b

(3x + 7)2 – 84x = (3x – 7)2

L.H.S. = R.H.S.

Hence, proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Deduce the AlgebrTamilnadu - Math Term-2

Find out the follTamilnadu - Math Term-2

If (x + a) (x + bTamilnadu - Math Term-2

i. If the values Tamilnadu - Math Term-2

If a + b = 5 and Tamilnadu - Math Term-2

Evaluate the follTamilnadu - Math Term-2

Evaluate the follTamilnadu - Math Term-2

Evaluate the follTamilnadu - Math Term-2

Evaluate the follTamilnadu - Math Term-2

Evaluate the follTamilnadu - Math Term-2